Pediatric consultation-liaison psychiatry : a description of the consultation-liaison service offered by a tertiary level children's hospital in Cape Town, South Africa - Henderson, Terri (Division of Child and Adolescent Psychiatry, 2014)
Includes abstract. Includes bibliographical references.